2020
DOI: 10.18488/journal.57.2020.91.24.37
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Extraction Solvents on the Antimicrobial Activity of Psidium Guajava (Guava) Leaves against Multi-Drug Resistant Bacteria Implicated in Nosocomial Infections

Abstract: This present work was designed to investigate the effect of different extraction solvents on the antimicrobial activity of Psidium guajava leaves against some multidrug resistant bacteria in nosocomial infections. The MDR isolates such as Pseudomonas aeruginosa, Escherichia coli, Staphylococcus epidermidis, Proteus mirabilis, Staphylococcus saprophyticus and Bacillus cereus were obtained from Microbiology department culture collection of Department of Microbiology University of Ibadan Nigeria and their identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It should be noted that a proper comparison between studies cannot be made, even if similar methodologies were used, since each author established the MIC differently, for example, Soliman et al ( 41 ) defined MIC as the lowest concentration that had granular appearing micro-colonies of growth instead of filamentous radiating colonies on solid agar; while for Hemeg et al ( 68 ) MIC was the lowest concentration of extract that resulted in no visible growth on the surface of the agar. In addition, we can also find multiple differences between the methods to measure the antimicrobial effect, for example, dos Santos et al ( 44 ) used a 0.1% resazurin solution, while Festus et al ( 67 ) analyzed bacterial growth based on turbidity.…”
Section: Antimicrobial Effects Of Psidium Guajava Lmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that a proper comparison between studies cannot be made, even if similar methodologies were used, since each author established the MIC differently, for example, Soliman et al ( 41 ) defined MIC as the lowest concentration that had granular appearing micro-colonies of growth instead of filamentous radiating colonies on solid agar; while for Hemeg et al ( 68 ) MIC was the lowest concentration of extract that resulted in no visible growth on the surface of the agar. In addition, we can also find multiple differences between the methods to measure the antimicrobial effect, for example, dos Santos et al ( 44 ) used a 0.1% resazurin solution, while Festus et al ( 67 ) analyzed bacterial growth based on turbidity.…”
Section: Antimicrobial Effects Of Psidium Guajava Lmentioning
confidence: 99%
“…However, the highest dose used in the studies analyzed was 160 mg/ml (160,000 ug/ml) by Festus et al ( 67 ), but the highest reported MIC was 40 mg /ml (40,000 ug/ml) for the bacteria Pseudomonas aeruginosa, Bacillus cereus, and Escherichia coli ( 67 ).…”
Section: Antimicrobial Effects Of Psidium Guajava Lmentioning
confidence: 99%